Social Entrepreneurship: Changing the world through Social Business Models - Monika Jain (Abhigyan, 2012)
Social entrepreneurship is a new model for the charitable sector. It is still based on the desire to change the world and make it a better place. Social entrepreneurship relies on sound business principle and those who use this model are not afraid to use sales and marketing principles to raise funds and increase public awareness of what they are doing. Traditional charitable organizations tend to shy away from promoting their own work. Although the terms are relatively new, social entrepreneurs and social entrepreneurship can be found throughout history. A list of a few historically noteworthy people whose work exemplifies classic "social entrepreneurship" might include Florence Nightingale (founder of the first nursing school and developer of modern nursing practices), Robert Owen (founder of the cooperative movement), and Vinoba Bhawe (founder of India's Land Gift Movement),Meera and Muzzaffar Ali who have done phenomenal work for social uplift have designed clothes with the idea of providing a vocation in Kotwara